Penanganan Anak Hiperaktif Melalui Permainan Edukatif Jigsaw Di Tk Pgri Juwiring Tahun Ajaran 2016/2017 - Melani, Endah; , Dra. Surtikanti.S.H, M.Pd (2017)
The purpose of this study is to investigate the handling of hyperactive children through educational games jigsaw in TK PGRI Juwiring Klaten Academic Year 2016/2017. Method in this research is descriptive qualitative case study research on hyperactive children in kindergarten PGRI Juwiring Klaten. The research subjects were the children in the kindergarten PGRI Juwiring experiencing symptoms of hyperactivity Gabriel. The technique of collecting data through observation, interviews and documentation. The results showed that Gabriel often running around the classroom, unable to pay attention to the teacher, look for toys that exist around it, do not want to share with friends and it was hard to concentrate. This is what shows that Gabriel showed hyperactivity, after therapy with educational games jigsaw, Gabriel has been able to focus on activities, can pay attention to the teacher's explanation, the motion can be controlled and also been able to work without the help of researchers jigsaw game. Keywords: Handling of Hyperactive Children, Games Educational Jigsaw